Three-dimensional polypyrrole induced high-performance flexible piezoelectric nanogenerators for mechanical energy harvesting. (1st March 2022) - Shi, Songhan; Pan, Zhongbin; Cheng, Yu; Zhai, Yizan; Zhang, Yiling; Ding, Xiangping; Liu, Jinjun; Zhai, Jiwei; Xu, Jingkun
Abstract: Flexible piezoelectric nanogenerators (FPNGs) have received tremendous attention in terms of harvesting mechanical energy and driving portable devices. However, the weak interactions and interfacial defects between the fillers and matrix hinder from improving the flexibility and electromechanical properties of the composites, which limits the practical applications of nanogenerators. In this work, high-performance FPNGs based on all-organic composite thin films comprising of three-dimensional polypyrrole (3D PPy) and poly(vinylidene fluoride -hexafluoropropylene) [P(VDF-HFP)] are fabricated for the first time. The composite films exhibit excellent ferroelectric and piezoelectric properties, mainly resulting from the strong interfacial bonding between 3D PPy and the P(VDF-HFP) matrix. As a result, the FPNG prepared from the composites loaded with 5 wt% 3D PPy achieve considerable piezoelectric outputs (average power density of 5.52 μW/cm 2 and peak power density of 10.84 μW/cm 2 ). Meanwhile, the FPNGs can effectively obtain mechanical energy from human activities and still show a stable output after continuous operation over 3000 cycles. This work provides a novel idea to design and fabricate high-performance FPNGs through introducing conductive polymers into the matrix. Graphical abstract: Image 1